KONTEKSTUALISASI IBADAH PENGHIBURAN PADA TRADISI SLAMETAN ORANG MENINGGAL DALAM BUDAYA JAWA - Dwi Andrianta; Stimson Hutagalung; Rolyana Ferinia (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2020)
For Javanese, ‘Slametan,’ the tradition of the dead, is a culture rooted in Javanese lives. This could be a challenge for those who became Christians because the tradition is not according to the Biblical principles regarding the condition of the dead. Therefore, this study aims to find a method that can link Javanese culture and Biblical principles so that there will be no distortion in social life and evangelistic efforts to preach the love of Jesus. A qualitative method is used in this study where observations and literature study collect data through books and journals related to the issues. So, as a result, the contextualization of consolation based on I Corinthians 9:20, the principle of “alike”, will be a method to eliminate the distortions by performing consolation service on the days when the Javanese practice the slametan tradition.